Pemanfaatan Media Pembelajaran Ipa Untuk Meningkatkan Motivasi Belajar Siswa DI SD Negeri 060928 Medan - Bintang Mahrani Abdullah; Fadhilah Hilmy Nasution; Khoiriah Marta Parapat ; Rizki Ramadhani; Safran Hasibuan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Learning media are all forms used for activities to convey information that can be seen, manipulated, heard, read or discussed. The aim of this research is to find out how to use science learning media to increase student motivation at SD Negeri 060928 Medan. This type of research is descriptive qualitative research based on observation. Observation is a systematic observation of human activities and physical settings where these activities occur continuously from natural activities in order to produce facts. The results of this research indicate that the use of learning media can significantly increase student motivation in learning science. Teachers are able to use learning media clearly and make students interested in learning.